Identificando a demanda e a oferta de crédito bancário no Brasil - Mário Jorge Mendonça; Adolfo Sachsida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This study aims to estimate the system of bank credit demand and supply in Brazil. Understanding how the balance is established in this market is the key to know the importance of the credit channel. Based on the aggregated data from June 2000 to August 2012 not only for firms but also for individuals we founded the following results. First, credit demand is pro-cyclical, reacting negatively to the unemployment and positively to GDP. Second, the price elasticity of demand for firms is higher for firms than for individuals, corroborating the fact that companies may have other sources of funding. Thirdly, it was not possible to determine the bank credit supply to individuals. This fact seems to indicate that there is no reverse causality in the personnel credit in the sense that, for this segment, the credit demand has no effect on the loan rate. Fourth, we observe the expected signs into default, the cost of funding and inflation in credit supply function in both segments. Finally, it appears that the introduction of payroll loans on personnel credit brought down the cost of the loan.
Keywords: E31; E52; E62; C32; 330; credit demand and supply; bank lending channel; balance sheet channel; endogeneity; method of instrumental variables; method of three stages